2014
DOI: 10.2147/hp.s54455
|View full text |Cite
|
Sign up to set email alerts
|

The role of PHD2 mutations in the pathogenesis of erythrocytosis

Abstract: The transcription of the erythropoietin (EPO) gene is tightly regulated by the hypoxia response pathway to maintain oxygen homeostasis. Elevations in serum EPO level may be reflected in an augmentation in the red cell mass, thereby causing erythrocytosis. Studies on erythrocytosis have provided insights into the function of the oxygen-sensing pathway and the critical proteins involved in the regulation of EPO transcription. The α subunits of the hypoxia-inducible transcription factor are hydroxylated by three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 133 publications
1
46
0
Order By: Relevance
“…This model may be of major importance in our understanding of tumor risk in patients carrying mutations in other genes belonging the HIF pathway. Indeed, patients with germline mutations in PHD2/EGLN1 and HIF2A/EPAS1 can develop pheochromocytomas or paragangliomas (equivalent to extra-adrenal pheochromocytomas) (4951). A comparative study of PHD2 mutations showed a differential regulation of HIF that perfectly fits with the model described here (52).…”
Section: Discussionmentioning
confidence: 99%
“…This model may be of major importance in our understanding of tumor risk in patients carrying mutations in other genes belonging the HIF pathway. Indeed, patients with germline mutations in PHD2/EGLN1 and HIF2A/EPAS1 can develop pheochromocytomas or paragangliomas (equivalent to extra-adrenal pheochromocytomas) (4951). A comparative study of PHD2 mutations showed a differential regulation of HIF that perfectly fits with the model described here (52).…”
Section: Discussionmentioning
confidence: 99%
“…This was initially demonstrated by the identification of human erythrocytosis patients with heterozygous LOF mutations in the PHD2 gene (Percy et al 2006(Percy et al , 2007Al-Sheikh et al 2008;Ladroue et al 2008). These mutations, it should be noted, typically affect residues that reside in the catalytic domain of the protein (Gardie et al 2014). Subsequent studies using global conditional knockout of the Phd2 gene demonstrated that it plays the dominant role, among the Phd paralogs, in the control of renal Epo (Minamishima et al 2008;Takeda et al 2008).…”
Section: The Hif Pathwaymentioning
confidence: 99%
“…Under normoxic conditions, HIF1A is hydroxylated by PHD2 (prolyl hydroxylase domain‐containing protein 2, also termed EGLN1), and subsequently degraded by the ubiquitine‐proteasome pathway in a von Hippel‐Lindau tumour suppressor (VHL)‐dependent manner. This exquisitely sensitive mechanism is perturbed by hypoxia, which, by inhibiting HIF1A hydroxylation, physiologically stimulates erythropoietin (EPO) synthesis, leading to red cell overproduction (Gardie et al , ).…”
Section: Patient Characteristics and Genotypesmentioning
confidence: 99%